Tolerogenic effect of non-inherited maternal antigens in hematopoietic stem cell transplantation - Hirayama, Masahiro; Azuma, Eiichi; Komada, Yoshihiro (Frontiers in Immunology, 2012)
Major histocompatibility complex antigens that provoke severe transplant reactions are referred to as the human leukocyte antigen (HLA) in human and as the H-2 in mice. Even if the donor and recipient are HLA-identical siblings, graft-versus-host reactions have been linked to differences in the minor histocompatibility antigen (MiHA). As the chance of finding an HLA identical sibling donor is only 25%, attention has been focused on using alternative donors. An HLA-mismatched donor with noninherited maternal antigens (NIMA) is less immunogenic than that with noninherited paternal antigens (NIPA), because the contact between the immune systems of the mother and child during pregnancy affects the immune response of the child against NIMA. However, the immunologic effects of developmental exposure to NIMA are heterogeneous, and can be either tolerogenic or immunogenic. We recently have devised a novel method for predicting the tolerogenic effect of NIMA. In this review, we overview the evidence for the existence of the NIMA tolerogenic effect, the possible cellular and molecular basis of the phenomenon, and its utilization in hematopoietic stem cell transplantation. We suggest a future direction for the safe clinical use of this phenomenon, fetomaternal tolerance, in the transplantation field.